2013
DOI: 10.1142/s0217751x13500462
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniversal Gaugino Masses and Natural Supersymmetry

Abstract: We demonstrate that natural supersymmetry is readily realized in the framework of SU (4)c ×SU (2) L ×SU (2) R with nonuniversal gaugino masses. Focusing on ameliorating the little hierarchy problem, we explore the parameter space of this model which yields small fine-tuning measuring parameters (natural supersymmetry) at the electroweak scale (∆ EW ) as well as at high scale (∆ HS ). It is possible to have both ∆ EW and ∆ HS less than 100 in these models, (2% or better fine-tuning), while keeping the light CP-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…In addition, when µ ≪ M 1,2 , these processes are largely insensitive to other SUSY parameters but higgsino mass µ. Therefore, we do not consider the production of stops and gluino in this paper, which contribute to the fine-tuning in more complicated and model-dependent way [19][20][21][22]. The current constraints on the mass limits of stop and gluino in natural SUSY have been discussed in [28][29][30][31][32][33].…”
Section: Calculations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, when µ ≪ M 1,2 , these processes are largely insensitive to other SUSY parameters but higgsino mass µ. Therefore, we do not consider the production of stops and gluino in this paper, which contribute to the fine-tuning in more complicated and model-dependent way [19][20][21][22]. The current constraints on the mass limits of stop and gluino in natural SUSY have been discussed in [28][29][30][31][32][33].…”
Section: Calculations and Discussionmentioning
confidence: 99%
“…(1.1), µ and m Hu must be of the order of ∼ 100 − 200 GeV, which implies light higgsinos. At the same time, the electroweak gaugino mass parameters M 1,2 are preferred to be of the similar order as the heavy gluino mass parameter M 3 and large Higgs-stop trilinear coupling A t is JHEP02(2014)049 needed [19][20][21][22]. Hence, generically we have µ ≪ M 1,2 and the mass splittings between the lightest chargino and the lightest two neutralinos at leading order are determined by [27] …”
Section: Introductionmentioning
confidence: 98%
“…It has been observed that this can reduce the hierarchy problem through the appearance of a new "focus point" that makes the Higgs mass less sensitive to the gaugino mass scale [16][17][18][19][20][21][22][23][24][25][26]. Here we explore this possibility in detail for both the MSSM and GNMSSM in the context of the latest LHC bounds on SUSY states and the measurement of the Higgs mass.…”
Section: Jhep11(2013)209mentioning
confidence: 99%
“…It is well-known that such a heavy gluino spoils the success of several models which consider the HB/FP region [64][65][66][67][68][69][70][71]. However, as we will show, this does not happen in our case.…”
Section: Sparticles Searchesmentioning
confidence: 61%